Glassless Augmented Display for Public Signage - SUZUKI, Hisataka; Shirai, Akihiko; Yanaka, Kazuhisa (International Journal of Virtual Reality, 2016)
This project realizes spatial augmented reality in public. We developed Glassless Augmented Display( GAD) which can show multiple different images to different direction simultaneously. Spatial augmented reality allows audiences to watch their preferred images and audios on public signage. It is a highly applicable technology configured by a consumer-based 4K liquid crystal display, superdirective speakers, a lenticular lens, and a multi-view image synthesizer implemented in a Unity application. We also proposed an application for GAD, which is called Simultaneous Spatial Shared Display (SSSD), which is implemented on Glassless Augmented Diaplay. SSSD enabled (1) simulmultiplex content display, (2) perspective correction, (3) without glasses and any sensing system, (4) directional audio for each content, and (5) attachable to conventional 2D display. These are used to display various contents, such as sports games and concerts, according to the movement of the audience.